Evaluation of Functioning Quality of Local Electrical Systems by the Criterion Method Based on Markov Processes - Lezhniuk, Petro; Komar, Vyacheslav; Sobchuk, Natalya; Sikorska, Olena (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The article proposes to use of a combination of the criterion method and Markov processes to evaluate the quality of functioning of renewable energy sources (RES) in the form of integrated readiness characteristic of the electricity network with RES or a local electrical system (LES). This is possible through the analysis of the problems of ensuring the quality of electricity supply in the conditions of intensive development of RES and defined by the qualimetric characteristics of the electricity networks, which are important for the provision of quality electricity. This contribute the development of generalized solutions and network development strategies, especially when it comes to building RES. The components of the integral index are determined as the probability of matching the actual regime to the "ideal". The "ideal" mode is determined on the basis of the principle of least action and corresponds to the circuit diagram of the network formed by the r-scheme. The basis thus determined in this way reduces the subjectivity of both evaluations and decisions taken on the basis of it.